RFID-Based Automatic Bus Ticketing: Features And Trends - Oudah, Ali A. (IOP Publishing, 2016)
Recent advancements in various technologies have made remarkable developments in various fields for public welfare and public transport is one such area. In the near future public bus transport system with advanced technologies like Radio Frequency Identification Device (RFID), GSM, GPS, ZigBee and RF modules will gain spotlight due to their advantage of higher convenience and greater life standards as compared to the conventional bus systems. In this paper, a comprehensive review of all several proposed bus ticketing and bus information methods has been presented in detail. The study brings out improved solution in terms of cost, convenience, user satisfaction and future implementation. The choice of working modules and their efficient performance has been discussed along with the highlighted importance of the need of technology for welfare of common public and visually impaired.